The Influence of Principals’ Instructional Leadership, Work Motivation, and School Culture on Elementary School Teachers’ Performance in Mranggen District, Demak Regency - Istiqomah, Istiqomah; Senowarsito, Senowarsito; Nuroso, Harto (FKIP - Universitas Riau, 2026)
This study examined the influence of principals’ instructional leadership, work motivation, and school culture on the performance of elementary school teachers in Dabin III, Mranggen District, Demak Regency. The study employed a quantitative approach with an ex post facto design. The population consisted of 139 teachers, and 103 teachers were selected as the sample using proportional random sampling. Data were collected through questionnaires, interviews, and documentation, and were analyzed using descriptive statistics, multiple linear regression, and coefficient of determination analysis. The findings revealed that principals’ instructional leadership, work motivation, school culture, and teacher performance were all categorized as very high. Simultaneously, instructional leadership, work motivation, and school culture had a significant effect on teacher performance. Partially, principals’ instructional leadership and school culture had a positive and significant effect on teacher performance, whereas work motivation did not have a significant effect. Among the independent variables, principals’ instructional leadership was the most dominant factor influencing teacher performance. The coefficient of determination showed that 56.8% of the variance in teacher performance could be explained by the three independent variables. These findings indicate that improving teacher performance requires strengthening instructional leadership and developing a positive school culture.